The effect of workplace spirituality on employees' contextual performance through work effectiveness - Gustari, Irvandi; Widodo, Widodo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Employee performance is crucial for organizational competitiveness and organizational performance. However, many employees cannot meet work standards and targets as performance parameters. Therefore, this research aimed to examine the relationship between workplace spirituality, work effectiveness, and employees’ contextual performance with mediation mechanisms. The research uses a quantitative approach with survey methods. The research used a questionnaire on a Likert scale. Data were collected from 430 employees in private companies across three provinces in Indonesia. The results from structural equation modeling (SEM) analysis showed that workplace spirituality, directly and indirectly, enhances employees’ contextual performance through work effectiveness. Furthermore, work effectiveness had a stronger direct influence on contextual performance than workplace spirituality. Work effectiveness is an essential mediator in translating workplace spirituality into heightened employee contextual performance. This evidence provides a theoretical contribution to the development of a study on the relationship between workplace spirituality and employee contextual performance through work effectiveness. It also has practical implications for company management in improving employee performance through the perspective of workplace spirituality and work effectiveness. Therefore, before being embraced, adjusted, and adapted to help research and practice in the future, it merits being utilized as material for critical discussion among scholars and practitioners.